Pedagogical Study of the Prophet Muhammad in the Hadith: Practical, Dialogical, and Analogical Approaches - Agung Cahya; Romlah Abubakar Askar; Munzir Suparta (Taqriri: Journal of Al-Hadith Science Studies, 2025)
This study examines the pedagogical approach of the Prophet Muhammad SAW in the hadith, focusing on three main methods: practical, dialogical, and analogical. These approaches are relevant in the current educational context because they prioritize direct interaction, in-depth understanding, and the application of learning concepts in everyday life. The study used a qualitative method with analysis of relevant hadith texts and a literature review on Islamic education. The results of the study indicate that the practical method applied by the Prophet SAW, through life examples, is very effective in transferring teachings in a concrete way. The dialogical approach, through questions and answers, increases the active involvement of students and deepens their understanding. The use of analogies or parables facilitates the understanding of abstract concepts, making them easier to understand by the people at that time. In conclusion, the pedagogical approach of the Prophet Muhammad SAW provides an important foundation for the development of more effective and relevant learning methods in modern education.